Kantowski-Sachs String Cosmological Model with Bulk Viscosity in General Scalar Tensor Theory of Gravitation. (23rd May 2013) - Rao, V. U. M.; Neelima, D.
Abstract : A new class of spatially homogeneous Kantowski-Sachs string cosmological models with bulk viscosity in Nordtvedt (1970) general scalar-tensor theory of gravitation with the help of a special case proposed by Schwinger (1970) is obtained. In this paper we have presented anisotropic as well as isotropic cosmological models. Some important features of the models, thus obtained, have been discussed. These exact models are new and more general and represent not only the early stages of evolution but also the present universe.